2014
DOI: 10.15252/emmm.201404402
|View full text |Cite
|
Sign up to set email alerts
|

Combined deletion of Pten and p53 in mammary epithelium accelerates triple‐negative breast cancer with dependency on eEF2K

Abstract: The tumor suppressors Pten and p53 are frequently lost in breast cancer, yet the consequences of their combined inactivation are poorly understood. Here, we show that mammary-specific deletion of Pten via WAP-Cre, which targets alveolar progenitors, induced tumors with shortened latency compared to those induced by MMTV-Cre, which targets basal/luminal progenitors. Combined Pten-p53 mutations accelerated formation of claudin-low, triple-negative-like breast cancer (TNBC) that exhibited hyper-activated AKT sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
103
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 81 publications
4
103
1
Order By: Relevance
“…In Drosophila, the first demonstration of cooperative tumorigenesis came from studies in which mutations in tumor suppressor genes, with altered cell polarity, showed neoplastic tumor growth in combination with the constitutive activation of the oncogene Ras85D (Ras85D V12 or Ras V12 ) (Brumby and Richardson, 2003;Pagliarini et al, 2003). Given that cooperation between two oncogenes or two tumor suppressor genes can also lead to hyperplasia or neoplasia (Briggs et al, 2008;Land et al, 1983;Liu et al, 2014), we considered whether the simultaneous loss of scrib and cno in clones could lead to a tumor-like overgrowth. Using the MARCM technique, we generated GFP-labeled cno R2 scrib 1 double-mutant clones in NBII lineages of late third instar larval brains.…”
Section: Resultsmentioning
confidence: 99%
“…In Drosophila, the first demonstration of cooperative tumorigenesis came from studies in which mutations in tumor suppressor genes, with altered cell polarity, showed neoplastic tumor growth in combination with the constitutive activation of the oncogene Ras85D (Ras85D V12 or Ras V12 ) (Brumby and Richardson, 2003;Pagliarini et al, 2003). Given that cooperation between two oncogenes or two tumor suppressor genes can also lead to hyperplasia or neoplasia (Briggs et al, 2008;Land et al, 1983;Liu et al, 2014), we considered whether the simultaneous loss of scrib and cno in clones could lead to a tumor-like overgrowth. Using the MARCM technique, we generated GFP-labeled cno R2 scrib 1 double-mutant clones in NBII lineages of late third instar larval brains.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the effect of pten loss on BC, we deleted pten using a floxed allele (pten fl ) (25) and the deleter line MMTV-Cre NLST , which targets stem/bi-potent progenitor cells, or WAP-Cre, which targets CD24-positive, pregnancy-identified stem cells/alveolar progenitors (26,27). As we previously described, tumors from these models were heterogeneous, consisting primarily of adenomyoepithelioma (AME) and other well-differentiated subtypes (13). Formation of secondary tumors following engraftment into host mice is a major hallmark of tumor aggressiveness (28).…”
Section: Resultsmentioning
confidence: 99%
“…To identify TICs, mammary tumors were dissociated into single cells using collagenase digestion, lineage depleted, sorted on the basis of specific cell surface markers, serially diluted, mixed with matrigel, and transplanted into mammary glands of young, immunocompromised mice. Using these conditions, we previously identified TICs in mouse models of her2/neu, wnt1, mammary-specific rb loss, p53 loss, and pten/p53 double mutants (13,29,30 Table 2). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ribosome half-transit time measurements were assessed as in [37,39] with the following modifications; 200,000 cells seeded for 24 h in 6-well plates were treated for 6 h with 20 lM NFR; after 5.5 h of treatment, medium was replaced with labeling medium (DMEM, with 4,500 mg/l glucose and sodium bicarbonate, and without L-methionine, L-cystine, and L-glutamine [Sigma-Aldrich], supplemented with 10% FCS, 1% nonessential amino acids (Gibco Life Technologies TM ), and 2 mM L-glutamine (AMIMED, Bioconcept)) for 30 min before addition of 1 lCi/well/ml of L- 35 Smethionine/cysteine. For cycloheximide treatment, CHX was added at 1 lg/ml to the labeling medium for 30 min.…”
Section: Ribosome Half-transit Time Measurementmentioning
confidence: 99%